Uniportal video‐assisted thoracic surgery could reduce postoperative thorax drainage for lung cancer patients. Issue 6 (15th May 2019) - Li, Jiagen; Qiu, Bin; Scarci, Marco; Rocco, Gaetano; Gao, Shugeng
Abstract : Background: Uniportal video‐assisted thoracic surgery (VATS) has undergone significant development in recent years, yet its usefulness and value in the treatment of lung cancer remains controversial. We investigated the effect of uniportal VATS surgery for reducing postoperative thorax drainage in lung cancer patients. Methods: The data of primary lung cancer patients who underwent VATS anatomical lung resection at the China National Cancer Center by a single surgeon were retrospectively collected. After propensity score matched analysis, 492 patients (246 uniportal VATS, 246 multiportal VATS) were included in the study. The clinicopathologic and surgery‐related features, including drainage volume, were compared. Student's t and chi‐square tests were used; all tests were two‐sided. Results: Patients in the two groups had similar demographic and clinicopathological features. Patients who underwent uniportal VATS surgery had significantly lower postoperative thorax drainage (830.0 ± 666.0 mL vs. 1014.5 ± 616.9 mL, P = 0.002) and a comparatively lower rate of unplanned return to the operating room (0 vs. 0.8%; P = 0.156) than multiportal VATS patients. The surgical duration, blood loss, number of lymph nodes dissected, postoperative complications, and length of hospital stay were similar between the groups. Conclusions: Uniportal VATS could reduce postoperative thorax drainage and the risk of unplanned return to the operating room for lung cancer patients. This study included the largest sample by a single surgeon and our results suggest the potential value of uniportal VATS for the faster recovery of lung cancer patients.